Growth and Development of China: A Developmental State 'With Chinese Characteristics'. Issue 3 (24th July 2021) - Karagiannis, Nikolaos; Cherikh, Moula; Elsner, Wolfram
Abstract: The aim of the paper is twofold: 1. to examine the identities and differences of the Chinese model of the developmental and entrepreneurial state 'with Chinese characteristics' with the general East Asian developmental state model, and 2. to derive some perspectives for the future of the particular Chinese model of the developmental state. The paper is structured as follows. The first main section briefly discusses China's growth performance and policies since World War II with respect to the country's development efforts. Subsequent sections analyse aspects of the particular economic development framework of China, based on an interventionist heterodox developmental state argument, and describe some critical development policy areas that emanate from such an argument—placing great emphasis on industrial targeting—while taking the country's socio-cultural and politico-institutional traits into consideration. Some conclusions end the paper.